2019
DOI: 10.1111/eci.13065
|View full text |Cite
|
Sign up to set email alerts
|

Associations of secreted phosphoprotein 1 and B lymphocyte kinase gene polymorphisms with autoimmune thyroid disease

Abstract: Background Dysregulation of the type 1 interferon (IFN)‐related signalling pathway predisposes one to autoimmune diseases. Possible associations of single‐nucleotide polymorphisms (SNPs) of secreted phosphoprotein 1 (SPP1) and B lymphocyte kinase (BLK) of the type 1 IFN‐related signalling pathway with autoimmune thyroid disease (AITD) in an ethnic Chinese (ie Taiwanese) population were tested. Methods Totally, 83 Hashimoto's thyroiditis (HT) patients, 319 Graves’ disease (GD) patients and 369 controls were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Secreted phosphoprotein 1 (SPP1) is a secreted glycophosphate protein with a wide range of functions and is also known as osteopontin, which plays an indispensable role in B cell-triggered cellular immunity [39,40]. At the same time, it plays a significant role in numerous autoimmune diseases, e.g., rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis [41]. Studies have shown that SPP1 levels in pyramidal neurons in the hippocampus of AD patients are significantly elevated [42].…”
Section: Discussionmentioning
confidence: 99%
“…Secreted phosphoprotein 1 (SPP1) is a secreted glycophosphate protein with a wide range of functions and is also known as osteopontin, which plays an indispensable role in B cell-triggered cellular immunity [39,40]. At the same time, it plays a significant role in numerous autoimmune diseases, e.g., rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis [41]. Studies have shown that SPP1 levels in pyramidal neurons in the hippocampus of AD patients are significantly elevated [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies indicated that BLK was linked to numerous autoimmune diseases, 15‐19 the relationship of BLK polymorphism with NMOSD predisposition has not been reported. To the best of our knowledge, this study is the first to explore the effect of genetic polymorphisms in BLK variants on NMOSD occurrence among the Chinese Han population.…”
Section: Discussionmentioning
confidence: 95%
“… 13 , 14 Furthermore, BLK is involved in the immune tolerance of B lymphocytes, affecting the function of B cells, which may lead to autoreactive or regulatory cellular responses, increasing the risk of autoimmune diseases. Most studies have provided reliable evidence that the single nucleotide polymorphisms (SNPs) of BLK exert a key role in susceptibility to various autoimmune disorders, such as SLE, 15 rheumatoid arthritis (RA), 16 SS, 17 thyroid disorders, 18 and systemic sclerosis. 19 Similarly, NMOSD is also mainly a B cell‐mediated autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…SPP1, also named osteopontin, plays an important role in cell-mediated immunity and immunoglobulin production by B cells [ 39 , 40 ]. It is involved in various autoimmune diseases including systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis [ 41 ]. It was demonstrated that SPP1 levels were increased in the serum of patients suffering from Graves’ disease [ 42 ].…”
Section: Discussionmentioning
confidence: 99%